2020
DOI: 10.1080/10503307.2020.1831097
|View full text |Cite
|
Sign up to set email alerts
|

Development of therapeutic alliance in mentalization-based treatment—Goals, Bonds, and Tasks in a specialized treatment for borderline personality disorder

Abstract: Objective: Mentalization-based treatment (MBT) is an evidence-based long-term treatment for borderline personality disorder (BPD). Alliance is central for effective psychotherapies. Few studies have addressed aspects of working alliance in BPD evidencebased treatments. This study aimed to investigate alliance development in MBT therapies with different clinical outcomes. Method: The sample included 155 patients in an MBT programme. Clinical outcomes were based on Global Assessment of Functioning (GAF). The sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 63 publications
2
18
0
Order By: Relevance
“…Also subsumed within this theme was therapists' commitment to MBT and the need to provide a strong therapeutic alliance. The alliance is a well‐evidenced common factor in psychotherapy (Wampold, 2015) and a potential mechanism of change in MBT (e.g., Folmo et al, 2021). Some therapists in our study talked about relational work with service users in the form of explicit discussion in the here and now about the therapeutic alliance (or mentalising relationship).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also subsumed within this theme was therapists' commitment to MBT and the need to provide a strong therapeutic alliance. The alliance is a well‐evidenced common factor in psychotherapy (Wampold, 2015) and a potential mechanism of change in MBT (e.g., Folmo et al, 2021). Some therapists in our study talked about relational work with service users in the form of explicit discussion in the here and now about the therapeutic alliance (or mentalising relationship).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to understanding therapists' general experiences of the therapeutic journey, it is important to understand common and specific mechanisms of change in MBT (e.g., the therapeutic alliance, enhanced mentalising, epistemic trust; Bateman & Fonagy, 2006; Folmo et al, 2021; Fonagy & Allison, 2014; Fonagy & Bateman, 2006), as perceived by the therapist. Drawing on therapists' own experiences of how their service users have changed or transitioned/adapted over the course of MBT could triangulate and extend the understanding we have gained from existing quantitative (De Meulemeester et al, 2018) and qualitative service user studies (e.g., Gardner et al, 2019) of the mechanisms of action, and thus guide future research into how MBT works.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study suggested high sensitivity to social exclusion as a predictor of poorer group alliance (Euler, Wrege, Busmann, Lindenmeyer, Kvarstein, 2018). Although not specifying group processes, a recent PD study highlighted interactions between the mutual agreement on aims and tasks in therapy and positive outcomes (Folmo, Stänicke, Johansen, Pedersen, et al, 2020).…”
Section: Gq As a Relevant Instrument For Pd Research And Treatment Mo...mentioning
confidence: 99%
“…Second, the alliance was measured at post-intervention. As such, we cannot preclude that the therapeutic alliance was not a moderator of improvements in PF, but that is was actually an outcome of improved PF in itself, given that previous process literature has shown that improvements in symptoms throughout therapy may lead to a better perceived therapeutic alliance (Ardito & Rabellino, 2011;Folmo et al, 2021). Third, the operationalization of our daily life PF measures consisted only of a limited number of ESM items, and our momentary measures focused solely on the open ACT processes.…”
Section: Limitationsmentioning
confidence: 99%